Poverty level analysis in East Nusa Tenggara Province - Frederic Winston Nalle; Margareta Diana Pangastuti (INOVASI, 2022)
East Nusa Tenggara Province is one of the poorest provinces in Indonesia and various government policy packages are being intensified to address this. Therefore, the aim of this research is to find out the dominant factors that influence the high number of poor people in East Nusa Tenggara Province. In an effort to answer the research problem, the analytical tool used is Panel Data analysis where the number of analysis units or cross section data are all districts/cities in NTT Province as many as 22 districts while for Time Series data starting from 2018-2021. The results of data analysis show that either partially or simultaneously each independent variable, namely economic growth,